2021
DOI: 10.4018/ijabim.20210701.oa15
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Medication Adherence Using TV Programmes as Reminders

Abstract: According to WHO, only 50% of patients adhere to chronic therapy. The problem of non-adherence has persisted over decades. Over 197 million Indian households have TV sets, and on average Indians spend 3 hours, 44 minutes watching television. A TV programme is used as intervention by patients to improve medication adherence rates. The objective of the research is to find the effect of TV programmes as a form of reminder in improving medication adherence. With the help of a structured questionnaire, the informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…These techniques show better rates of improvements than non-interactive interventions [ 16 ]. Medication adherence is a complex behavior which differs across patient categories [ 17 ]. Factors like patient beliefs, perception about side effects, patient physician relationship, importance given to physician instructions, disease type, severity of disease, etc.…”
Section: Introductionmentioning
confidence: 99%
“…These techniques show better rates of improvements than non-interactive interventions [ 16 ]. Medication adherence is a complex behavior which differs across patient categories [ 17 ]. Factors like patient beliefs, perception about side effects, patient physician relationship, importance given to physician instructions, disease type, severity of disease, etc.…”
Section: Introductionmentioning
confidence: 99%
“…(Al-Ganmi et al, 2020). Several researchers have used ratio analysis to study the effect of interventions on diseases (Foroutan et al, 2020;Saha et al, 2021cSaha et al, , 2021a. A study using the ratio analysis technique found that exposure to pets and farm animals helped reduce acute lymphoblastic leukemia risk among children (Figueroa et al, 2020).…”
mentioning
confidence: 99%